Developing Lesson Plan For Blended Interactive Teaching Descriptive Text at Seventh Graders - Fahmi Al Fiqri; Farouk Imam Arrasyid; Zakky Yavani (Syntax Corporation, 2022)
This article examined the lesson plan's poor quality, which hinders language learning because it's only an administrative necessity. The study team set goals. Recognising and designing a lesson plan. This study used the three-stage R&D model of feasibility (need analysis), product development, and validation. Qualitative data analysis improves comprehension, comparison, and interpretation. Comparing questionnaire results led to study conclusions.The study found that students' learning styles have never been used to build effective teaching and learning tactics. Researchers use project-based, social-family, and student-centered learning. The results show that the researchers only employ 16 of the 20 characteristics to develop the lesson plan. Facilitators should also promote student-centered and project-based learning.